Isolation of Microorgansims from the Air Conditioning System in Cars - sulail, Hedaiah Jassim; Al-Beladi, Hashmiah Hussain; Al-Dossary, Reem Abdullatif; Al-Anezi, Nouf Hezam; Al-Sidrah, Bader Kalid; Al-Dawood, Yahya; Al-Saleh, Abdulmonem; Ahmed, Nadir; Mohamed, DeyaEldin; Babakir, Sara; Al-Ibrahim, Noura Naji; Al-Said, Fatimah; et al. (Journal of medical and pharmaceutical sciences, 2022)
Background and Objectives: Automobile air-conditioning (AC) systems are cooling equipment used in modifying air temperature inside the car. AC also can be a major source of the microbial contamination which may bring health risks to users, either by hypersensitivity or infections. This research aimed to assess the air quality inside automotive in Dammam, Eastern Province, Saudi Arabia (MACHS College). It was carried out with 34 and 3 randomly selected cars and buses, respectively (MACHS parking area). Materials and Methods: The air samples are collected starting from 9 Feb up to 27 Feb 2020 by exposing two types of Petri dishes (Blood agar and Sabouraud Dextrose agar) in front of air conditioning for 5 minutes. Dishes were incubated at 37℃ for three day and 30 oC for one day for bacteria and fungi respectively. Results: There were deferent Bacterial species (gram positive) and many fungal species (Aspergillus spp, and yeast) found. There were significant relationships between the old car filter with both bacterial and fungal growth. There was a relationship between the cars’ age and the presence of bacterial growth. There was no relationship observed between the cars’ age and the fungal growth. There were no relationships between the cars’ odometer reading and the presence of bacterial and fungal growth.